Modeling the Western Iberian margin circulation: present and future - Pires, Ana Cordeiro (2013)
The purpose of this work is to carry out a comprehensive study on the Western Iberian Margin (WIM) circulation my means of numerical modeling, and to postulate what this circulation will be in the future. The adopted approach was the development of a regional ocean model configuration with high resolution, capable of reproducing the largeand small-scale dynamics of the coastal transition zone. Four numerical experiences were carried out according to these objectives: (1) a climatological run, in order to study the system’s seasonal behavior and its mean state; (2) a run forced with real winds and fluxes for period 2001-2011 in order to study the interannual variability of the system; (3) a run forced with mean fields from Global Climate Models (GCMs) for the present, in order to validate GCMs as adequate forcing for regional ocean modeling; (4) a similar run (3) for period 2071-2100, in order to assess possible consequences of a future climate scenario on the hydrography and dynamics of the WIM. Furthermore, two Lagrangian particle studies were carried out: one in order to trace the origin of the upwelled waters along the WIM; the other in order to portrait the patterns of larval dispersal, accumulation and connectivity. The numerical configuration proved to be adequate in the reproduction of the system’s mean state, seasonal characterization and an interannual variability study. There is prevalence of poleward flow at the slope, which coexists with the upwelling jet during summer, although there is evidence of its shifting offshore, and which is associated with the Mediterranean Water flow at deeper levels, suggesting a barotropic character. From the future climate scenario essay, the following conclusions were drawn: there is general warming and freshening of upper level waters; there is still poleward tendency, and despite the upwellingfavorable winds strengthening in summer the respective coastal band becomes more restricted in width and depth. In what concerns larval connectivity and dispersion along the WIM, diel vertical migration was observed to increase recruitment throughout the domain, and while smooth coastlines are better suppliers, there is higher accumulation where the topography is rougher.